Spatial Distribution, Bioconversion and Ecological Risk of PCBs and PBDEs in the Surface Sediment of Contaminated Urban Rivers: A Nationwide Study in China - Lu, Qihong; Liang, Yongyi; Fang, Wenwen; Guan, Ke-Lan; Huang, Chenchen; Qi, Xuemeng; Liang, Zhiwei; Zeng, Yanhong; Luo, Xiaojun; He, Zhili; Mai, Bixian; Wang, Shanquan (Environmental science & technology, 2021)
Surface sediments of polluted urban rivers can be a reservoir of hydrophobic persistent organic pollutants (POPs). In this study, we comprehensively assessed the contamination of two groups of POPs, that is, polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs), in 173 black-odorous urban rivers in China. Spatial distribution of PCBs and PBDEs showed similar patterns but very different contamination levels in surface sediments, that is, average concentrations of 10.73 and 401.16 ng/g dw for the ∑PCBs and ∑PBDEs, respectively. Tetra-/di-CBs and deca-BDE are major PCBs and PBDEs and accounted for 59.11 and 95.11 wt % of the ∑PCBs and ∑PBDEs, respectively. Compared with the persistence of PBDEs, the EF changes of chiral PCBs together with previous cultivation evidence indicated indigenous bioconversion of PCBs in black-odorous urban rivers, particularly the involvement of uncharacterized Dehalococcoidia in PCB dechlorination. Major PCB sources (and their relative contributions) included pigment/painting (25.36%), e-waste (22.92%), metallurgical industry (13.25%), and e-waste/biological degradation process (10.95%). A risk assessment indicated that exposure of resident organisms in urban river sediments to deca-/penta-BDEs could pose a high ecological risk. This study provides the first insight into the contamination, conversion and ecological risk of PCBs and PBDEs in nationwide polluted urban rivers in China.